Identification of storm rainfall pattern of Sungai Ara catchment - Omar, Ruzlina (2003)
Rainfall is a nominal phenomenon in Malaysia which is situated near the equatorial line. The total rainfall that Malaysia receive every year are quite high which is between 2000mm to 2500mm. Every rainfall event produce different pattern and characteristics. The study undertaken was to determine the typical storm rainfall pattern at Sungai Ara Catchment, Wilayah Persekutuan, Malaysia. This study only consider storm rainfall which the total depth of rainfall more than 10mm. The study was carried out based on the rainfall data of five minutes interval in year 2000 and 2001. The rainfall data is obtained from the Department of Irrigation and Drainage Ampang which are recorded from 13 station automatic rainfall gauges. The main objective of this study is to know the typical storm rainfall pattern of the studied area. The methodology is by plotting the graph of percentage cumulative rainfall depth versus percentage cumulative time. Then the 45° line are added to show the idealised storm rainfall pattern. The curve above the 45° line will be categorised as positive condition and the curve below the 45° line will be categorised as negative condition. The result of this study found that the typical storm rainfall pattern is simple which there are only two curve. The curve start with negative condition which are below the 45° line and then it turned to the positive condition which are above the 45° line. The typical hyetograph pattern has only one peak point and situated between 20% to 40% of cumulative time.